Prenatal and postnatal babesiosis in calves - Iskandar, Fatimah; K., Ragavan; Abdul Rahman, Sheikh Omar; Ungku Mohsin, Ungku Chulan; Fateh Mohamed, Bashir Ahmad (Persatuan Doktor Veterinar Malaysia, 1984)
Nine cases of babesiosis in calves of local breeds or their crossbreds between the ages of 5 to 112"days are reported. Three of these calves were suspected of having acquired a prenatal infection. 71,e organisms involved were Babesia bovis and Babesia bigemina.